IMPORTANCE OF PHARMACEUTICAL ASSISTANCE IN ACCESS TO ONCOLOGICAL TREATMENT - Menezes de Lima, Dafné; Carlos da Silva, Erika; Maria de Amorim Santos, Eva; Nunes Santana de Miranda, Jaciele; Nunes Santana de Mmiranda, Jamile; de Souza Pereira, Malvina; Natágoras Alves de Albuquerque, Marcone; Santos de Matos, Thainá; Dannylo Macedo Rodrigues, Welber; Wilker Eufrásio do Nascimento, José (Health and Society, 2023)
Cancer is the common name given to a group of pathologies where disordered growth of cells occurs, which can penetrate into other tissue parts or spread to other regions of the body. This work has as objective the pharmacist and the pharmaceutical assistance in the oncological treatment. This study refers to an integrative literature review of the explanatory type, of a qualitative nature. In this literature review, the construction of research will be carried out through six phases, such as: delimitation of the theme and choice of hypothesis or guiding question, establishing a delimitation for an effective data search. Therefore, with the completion of this project, it is expected to obtain a literature review in which it is intended to identify the importance of hospital clinical pharmaceutical care in oncological patients and its evolution in pharmaceutical legislation and, for that, to describe the activities attributed to the pharmacist within its scope. private jurisdiction.